Process Evaluation of an Online SUpport PRogram for Older Hearing Aid Users Delivered in a Cluster Randomized Controlled Trial - Meijerink, Janine F. J.; Pronk, Marieke; Lissenberg-Witte, Birgit I.; Jansen, Vera; Kramer, Sophia E. (Frontiers in Medicine, 2021)
Objectives: To evaluate the process of implementing a web-based support program (SUPR) for hearing aid users in the Dutch dispensing setting in order to allow interpretation of the randomized controlled trial’s results (positive effects on hearing-aid related outcomes; no effects on psychosocial outcomes). Design: Measures: Context of implementation, recruitment, SUPR’s: reach, implementation fidelity, dose delivered, dose received, satisfaction, and benefit. Data collection: Quantitative and qualitative. Study sample: One hundred thirty-eight clients (mean age 68.1 years; 60% male) and 44 dispensers completed questionnaires. Five clients and 6 dispensers participated in interviews and focus groups. Results: Clients and dispensers were generally satisfied with SUPR’s usefulness. SUPR-videos were watched by 7-37% of the clients. Around half of the dispensers encouraged clients to watch them or informed them about SUPR. Some clients found the SUPR- materials suboptimal, and changes in personnel and limited dispenser-training were barriers acting on a contextual level. Conclusions: This study identified several factors that contributed to the success of SUPR. Others factors, acting on various levels (e.g., intervention material, dispensers, and implementation context), were suboptimal and may explain the absent psychosocial effects. The identified factors are important to consider in further development of SUPR, and in other web-based support programs.